2011
DOI: 10.1259/dmfr/85845119
|View full text |Cite
|
Sign up to set email alerts
|

Deriving Hounsfield units using grey scale of a CBCT?: author response

Abstract: We appreciate the reader's interest in our research paper "Deriving Hounsfield units using grey levels in cone beam computed tomography" in the September 2010 issue of DMFR. 1 We have subsequently applied this method in a clinical situation and the results will be submitted shortly for publication by the same authors. This should help to explain some of the issues raised in this letter to the editor.We are aware of the paper by Bryant J A et al 2 and we will attempt to address some of the issues regarding non-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…While a CBCT scan is also useful in determining bone quantity, bone height and proximity of adjacent structures, it lacks the ability to quantify bone quality in a meaningful manner. This study has demonstrated a clinical application of a method developed by Mah et al 9 to derive Hounsfield units using grey levels in the CBCT volume. The application of this method to derive Hounsfield units can provide a standardized method to assess bone quality similar to that found in medical CT.…”
Section: Discussionmentioning
confidence: 93%
See 4 more Smart Citations
“…While a CBCT scan is also useful in determining bone quantity, bone height and proximity of adjacent structures, it lacks the ability to quantify bone quality in a meaningful manner. This study has demonstrated a clinical application of a method developed by Mah et al 9 to derive Hounsfield units using grey levels in the CBCT volume. The application of this method to derive Hounsfield units can provide a standardized method to assess bone quality similar to that found in medical CT.…”
Section: Discussionmentioning
confidence: 93%
“…While the original grey level values are not realistic Hounsfield units it is at least possible to distinguish between the two kinds of bone. Figure 5 shows the distribution of ''corrected'' grey levels using the method of Mah et al 9 While the average values for the two materials are now realistic Hounsfield units, the variability of effective energies results in such a tremendous overlap between the values of the two materials that it is difficult to distinguish one from the other. This variability would seem to be a serious deficiency in this method of calibration.…”
Section: Figuresmentioning
confidence: 99%
See 3 more Smart Citations